Essays on the performance of South African Real Estate Investment Trusts (REITs) - Ajayi, Oluwaseun Damilola (My University, 2022)
A lot of attention has been paid recently to the performance of REITs (real estate investment trusts). REITs' performance in emerging economies (especially South Africa) has been the subject of several studies, although the results have been mixed. The study conducts three separate empirical studies that cover the following aspects of REITs performance: (a) the degree of secondary equity offerings (SEOs) underpricing of Black Economic Empowerment (BEE) REITs versus non-BEE REITs; (b) earnings management among internally and externally managed REITs; and (c) the female inclusion and level of education on boards of REITs and financial performance. This thesis consists of three independent essays. First essay investigates the degree of Secondary equity offerings (SEOs) underpricing of Black Economic Empowerment (BEE) Real estate investment trusts (REITs) versus non-BEE REITs. In the paper (essay), 152 SEOs issued by 21 REIT firms (based on availability of data) from January 1, 2010 to December 31, 2020 were retrieved from the Stock Exchange News Service (SENs) of the Johannesburg Stock Exchange (JSE). Using OLS regression in analysing our data, evidence indicates that higher BEE compliance is positively related to SEO underpricing; in other words, SEOs of BEE compliant REITs are more underpriced compared to noncompliant BEE REITs. Evidence also suggests that the BEE policy needs to be recalibrated owing to its politicization as this will enhance compliance from REITs; yet, the study confirms that government ultimately benefits from SEOs of compliant firms which aids the implementation of both economic and political objectives. Compliant REITs continue to leave more money on the table; hence, the high rate of underpricing is not in their best interests. Government must therefore assist compliant firms with incentives. With these, compliant firms will need not have concerns about the extent of underpricing with Government’s intervention. This is a pioneer attempt at providing insights for subsequent studies of this nature. Second essay provides an empirical examination of earnings management among internally and externally managed REITs. The empirical accounting literature claims that internal management of a firm does not constrain earnings management, while others argue in favour of internal management for firms. Using a sample of listed South African REITs for the 2013 - 2021 time period, the study examines the relationship between management structures and earnings management. The study finds no aggressive practice in internally managed REITs during the study period. The focus on real activity-based earnings management suggests new avenues for research on management structures of firms. The results offer some insights for policy makers interested in promoting and strengthening legislation to ensure strong corporate governance in their respective nations. Third essay provides an empirical examination on female inclusion and level of education on boards of REITs and financial performance. This essay investigated the relationship among female inclusion, level of education on financial performance in a South African REIT board context. The study applies an ordinary least squares (OLS) approach to a unique panel dataset of 35 South African REITs over the period 2013–2021. The study also finds evidence of an insignificant relationship between gender diversity and REITs financial performance; meanwhile, the study found a significant relationship between female directors’ level of education and REITs performance; by implication, the results show that a REIT’s likelihood of having a woman on the board of directors does not necessarily increase financial performance (measured by ROA) while also revealing that having females with a higher education degree (Doctoral and Masters degree) improves performance of REITs. It also provides evidence for REITs managers as the study recommends current and future REITs to employ more women with degrees in higher education.
A thesis submitted in fulfilment of the requirements for the degree of Dotor of Philosophy to the Faculty of Engineering and Built Environment, School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2022